PENYULUHAN KESEHATAN TENTANG MANAJEMEN PEMBUANGAN SAMPAH YANG BAIK BAGI SISWA SDN 1 MOTONG BETOK - Purwanto, Rudi (Insanta : Jurnal Pengabdian Kepada Masyarakat, 2024)
Waste is the remaining waste resulting from a production process, both industrial and domestic. The objectives of providing Health Education regarding Good Waste Disposal Management are as follows: 1. To provide education regarding the meaning of waste, characteristics of waste in schools, waste management, good and correct waste management planning in schools. 2. To provide knowledge to students about the importance of keeping the surrounding environment clean. The result of this activity is that the students of SDN 1 Motong Betok have knowledge and skills regarding the meaning of waste, the characteristics of waste in schools, waste management, good and correct waste management planning in schools. Apart from that, from the results of the counseling, students understand the content of the material on how to differentiate organic and non-organic waste, how to recycle waste so that it is useful, and what a good form of trash can should be.